A Novel Single Sensor Variable Step Size Maximum Power Point Tracking for Proton Exchange Membrane Fuel Cell Power System. Issue 2 (9th April 2019) - Harrag, A.; Bahri, H.
Abstract: This paper proposes a novel single sensor variable step size maximum power point tracking (MPPT) method for proton exchange membrane (PEM) fuel cell. This paper is a first, if modest, attempt to develop a single sensor MPPT for fuel cell systems. The proposed MPPT algorithm uses only one sensor to track the maximum power of PEM fuel system composed of 7 kW proton exchange membrane fuel cell (PEMFC) powering 50 Ω resistive load via a DC–DC boost converter driven using the proposed MPPT. The performances of the proposed controller have been evaluated using the implemented PEM fuel cell power system Matlab/Simulink model using two test scenarios considering temperature and hydrogen pressure variation. Simulation results show that the proposed controller can effectively track the maximum power point using only one sensor which reduces the cost as well as the complexity of the PEM fuel cell power system. Comparative results with the two sensors MPPT show that the two sensors MPPT outperforms the single sensor MPPT regarding the dynamic performances. However, the proposed single sensor MPPT performs better considering the static performances. In addition, the proposed controller reduces drastically the current ripple increasing by the way the fuel cell efficiency and lifetime by reducing the frequent trip due to over‐current and even harmonics.